Estimation of uric acid in Iraqi women with breast cancer (Journal of the College of Basic Education, 2022)
Breast cancer is the most popular cancer among women and one from the central causes of death between women worldwide although not traditionally considered a tobacco-related cancer, many in vitro and in vivo studies implicate tobacco smoke as a potential breast cancer carcinogen. The results show a significant increase in uric acid at( p<0.05) in both of benign and malignant groups in relation to the controls, it is also observed that there is a non-significant changes (p>0.05) in radiotherapy group. However, smoking shows a non-significant changes of control with patient results of other groups p(>0.05). In conclusion results proposed this is may be a slight increase uric acid levels used to follow the effectiveness of treatment.